2012
DOI: 10.4315/0362-028x.jfp-11-561
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curing Method and Freeze-Thawing on Subsequent Growth of Listeria monocytogenes on Cold-Smoked Salmon

Abstract: The presence of the foodborne pathogen Listeria monocytogenes on cold-smoked salmon is a major concern for the seafood industry. Understanding processing and postprocessing handling factors that affect the ability of this pathogen to grow on cold-smoked salmon is critical for developing effective control strategies. In this study, we investigated the effect of curing method and freeze-thawing of cold-smoked salmon on (i) physicochemical properties and (ii) subsequent growth of genetically diverse strains of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Other authors indicated that L . monocytogenes was also able to grow on various fish products at refrigeration temperatures, and a similar increase was also observed in smoked salmon (Kang et al , 2012; Ferreira et al ., 2014). …”
Section: Resultssupporting
confidence: 58%
“…Other authors indicated that L . monocytogenes was also able to grow on various fish products at refrigeration temperatures, and a similar increase was also observed in smoked salmon (Kang et al , 2012; Ferreira et al ., 2014). …”
Section: Resultssupporting
confidence: 58%
“…The key differences between the reference condition that we used and CSS were that the CSS was vacuum packaged while the reference medium was not anaerobic (though MBHIB was incubated without shaking), L. monocytogenes was grown on the surface of CSS, while growth was planktonic in the liquid MBHIB, and CSS contains a number of unique components that cannot be easily added to BHIB at comparable concentrations (e.g., different phenolics, lipids, trace elements, etc.). In addition, a previous study in our lab on the same batch of CSS demonstrated that the resident lactic acid bacteria were able to grow to ϳ7 log CFU/g by day 10 (with an initial density of ϳ4 log CFU/g on day 0) under the same growth conditions as those used in the current study (31). Lactic acid bacteria are known to be one of the dominant microbes on CSS and may constitute a natural form of antimicrobial control via competition for particular nutrients or production of organic acids, hydrogen peroxide, and bacteriocins (64)(65)(66).…”
Section: Discussionmentioning
confidence: 83%
“…The concentration of lactic acid bacteria on uninoculated CSS was ϳ4 log CFU/g on day 0, ϳ6 log CFU/g on day 5, and ϳ7 log CFU/g on day 10 during incubation of the vacuum-packaged slices at 7°C. For the uninoculated CSS, the pH was ϳ6.18, water activity (a w ) was 0.96, moisture content was ϳ63.58%, and fat content was ϳ8.87% (31). Uninoculated salmon samples were plated onto Oxford agar and incubated at 30°C for 48 h to confirm the absence of L. monocytogenes.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, they described the modelling approaches as more expensive, since they require larger set ups and more complicated data analysis, but more advantageous, since they provide more information and allow prediction of growth/no growth under different circumstances. Kang et al (2012) investigated the effect of curing method and freeze-thawing of cold-smoked salmon on subsequent growth of genetically diverse strains of L. monocytogenes (inoculated after freezethawing). Wet-cured and dry-cured cold-smoked salmon fillets were cut into slices of~25 g and surface-spread inoculated with individual L. monocytogenes strains at a final concentration of 10 4 CFU/g.…”
Section: Challenge Tests In Seafoodmentioning
confidence: 99%